Beyond Quantification of Poverty: Emerging Issues in Poverty Reduction - Radhakrishna, R.; Rao, V.M.; Ray, Shovan (Indian Journal of Labour Economics, 2004)
In talking about poverty, the emphasis is now shifting from the poverty line (income poverty) to a view of poverty as an outcome of multiple deprivations. The stakeholders like NGOs, activists and funding agency personnel have now a substantial presence in the field exerting pressure on the policy maker to modify the top-down approach in the direction of making it more consultative and less centralised. There are also pressures on the policy maker to activate panchayats and to promote institutions-like self-help groups and user groups-helping the poor to participate in development processes and to mobilise them for collective action. In this changing context, this paper argues the need for a perspective viewing the poor as part of a wider society with links and relatioships affecting the economic conditions and development status of the poor. These links and relationships include poverty generation and poverty sustaining processes and structures besides poverty reduction strategies.
Keywords: Labour Economics; Poverty; Poverty Reduction